Tazkiyatun Nafs Karakter Tokoh dalam Cerita "Minadz Dzulumati Ila Nur" Karya Saddam Fathan Rasyidin - Arvi Farand Arkani; Najwa Jauharulmanik; Salma Fitriyani; Wiwin Handayani; Dadan Firdaus (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This research aims to analyze the concept of tazkiyatun nafs and the process of character transformation in the short story "Minadz Dzulumati Ila Nur" by Saddam Fathan Rasyidin. This research employs descriptive qualitative approach with an interpretative method and integrating the perspective of akhlak tasawoof by Imam al-Ghazali and literary psychology by Rene Wellek and Austin Warren. The data were collected through documentation and analyzed using content analysis. The findings reveal that the main character undergoes a gradual transformation through three phases, the empty phase, the dark phase, and the enlightened phase. This transformation aligns with the stages of tazkiyatun nafs in al-Ghazali’s framework, such as taubah, patience, tawakkal, and ikhlas. In literary psychology perspective, the character development is influenced by both internal conflict and external factors, such as the social environment. This research concludes that tazkiyatun nafs is a dynamic and continuous process that involves both spiritual and psychological dimensions in shaping an individual’s character.